Perspektif Maqashid Al-Syari’ah Jamaluddin Al-‘Athiyyah terhadap Urgensi Restorative Justice sebagai Alternatif Penyelesaian Kasus KDRT - Afizatul Mua'malah (Jurnal Hukum Lex Generalis, 2025)
Domestic Violence (DV) remains a serious social and legal problem in Indonesia, with impacts that not only physically and psychologically injure victims, but also damage the foundations of family life and threaten social stability. Although there is a legal umbrella in the form of Law Number 23 of 2004 concerning the Elimination of Domestic Violence, its implementation still faces obstacles, such as a weak response from law enforcement officials, a complicated evidentiary process, and formal justice that often adds to victims' trauma. This condition indicates the urgency of an alternative approach that is more humane, participatory, and recovery-oriented, one of which is through the implementation of Restorative Justice. This study aims to analyze the urgency of implementing Restorative Justice in resolving domestic violence cases in Indonesia and examine its relevance to the theory of Maqashid al-Syari'ah Jamaluddin al-'Athiyyah as an effort to protect families and maintain social welfare. The method used is normative juridical research with a conceptual and legislative approach. The research findings demonstrate that Restorative Justice has significant urgency as a legal instrument capable of delivering substantive justice for victims of domestic violence, maintaining family integrity, and preventing social harm, provided it is implemented carefully, with the principles of victim protection, voluntary action, and non-discrimination. From a maqasid perspective, Restorative Justice aligns with the objectives of sharia (Islamic law) in safeguarding life, honor, posterity, and the welfare of the community, making it a strategic alternative in realizing a more just and sustainable system for resolving domestic violence.